A distributed maximal link scheduler for multi Tx/Rx Wireless Mesh Networks - Wang, H.; Chin, K.; Raad, R.; Soh, Sie Teng (2014)
Recently, researchers have developed Wireless Mesh Networks (WMNs) where each router is capable of performing multiple transmissions or receptions concurrently; aka Multi Tx-Rx (MTR) WMNs. Consequently, each node is able to transmit (Tx) or receive (Rx) to/from its neighbors simultaneously. A fundamental problem in such WMNs is to derive a transmission schedule with minimal superframe length to maximize network capacity and minimize end-to-end delays. Unfortunately, deriving a minimal superframe length is equivalent to solving the NP-complete, MAX-CUT problem. To this end, there are a number of centralized schedulers, but only but only one distributed scheduler, called JazzyMAC. Henceforth, in this paper, we add to the state-of-the-art by proposing Algo-d, a novel distributed scheduler that solves the MAX-CUT problem using only local information. Experiment results show Algo-d generates superframes that are 37.5% shorter and it activates 264% more links as compared to JazzyMAC. Lastly, as compared to centralized schedulers, Algo-d schedules 50% more links than Algo-1 and at most 7% fewer links than Algo-2.